Teachers’ Strategies in Teaching Reading Comprehension to the Second-Grade Students of Senior High School - Anggi Oktavia Nur HS; Kisman Salija; Munir Munir (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The purpose of this study is to find out teacher strategies in teaching reading comprehension at SMAN 2 Jeneponto. Based on the research problem, it is evident that the purpose of this study is to describe the tactics employed by English teachers in teaching English to second-grade students at Senior High School 2 Jeneponto. This study is descriptive qualitative. Observation interviews and documentation were used to compile the data. The tactics for improving students' reading skills were based on Jeremy Harmer's premise of teaching reading: